Evaluation of vegetation and soil saturation in the Ventanilla Wetlands Regional Conservation Area using remote sensing in Peru, 2006-2021 - Camas Guardamino, David Josias (2022)
[Introduction]: In 2006, the Peru government created the Ventanilla Wetlands Regional Conservation Area (RCA) to conserve a representative sample of wetlands, protect soils and vegetation, prevent degradation and biodiversity loss, and promote their economic and academic use. [Objective]: The aim was to evaluate the RCA in what it was its buffer zone from months before its creation to 2021 by using remote sensing tools (ICEDEX and NDVI) to assess the state of vegetation and soil saturation. [Methods]: It consisted in the delimitation of the study area, acquisition of satellite images, pre-processing and processing of the images by using vegetation and soil saturation indexes and unsupervised classification, and interpretation of the results. [Results]: We found that about soil saturation there was a loss of 45.99 ha and a gain of 18.63 ha, the loss was accentuated in the northern zone of the RCA and the gain in the coastal strip, meanwhile for vegetation there was a gain of 27.63 ha and a loss of 5.04 ha, the gain was mainly in the coastal strip and the loss in the limits of the RCA. This evidence a process of eutrophication in the RCA, possibly due to anthropogenic causes, which are the main threats to this ecosystem. [Conclusions]: The variation of vegetation and soil saturation since the creation of the RCA was demonstrated by remote sensing tools and these suggest a possible eutrophication process that should motivate increased efforts for the conservation of this ecosystem.